On the Discounted Penalty Function for Claims Having Mixed Exponential - Šiaulys, J.; Kočetova, J. (Nonlinear Analysis: Modelling and Control, 2006)
It is considered the classical risk model with mixed exponential claim sizes. Using known results it is obtained the explicit expression of the GerberShiu discounted penalty function ψ(x,δ) = E e −δT 1(T < ∞) , by some infinite series. Here δ > 0 is the force of interest, x – the initial reserve and T – ruin time. The dependance of the discounted penalty function on the main parameters x, θ, λ, δ, α, σ, ν is presented in diagrams, where λ > 0 is the parameter of Poisson process, θ > 0 is the safety loading coefficient, 0 ≤ α ≤ 1 and σ, ν > 0 are the parameters of the mixed exponential distribution